ECONOMIC GLOBALIZATION AS A CHARACTERISTIC FEATURE OF THE XXI CENTURY - Zarema Daudova; Vitaly Lang (Вестник Северо-Кавказского федерального университета)
This article discusses the prerequisites for development, theoretical and methodological aspects and principles of modern globalizing world economy. The directions of the uneven distribution of benefits and the damage caused by globalization. It was found leads to increased globalization of homogeneity or heterogeneity mirotselostnosti. It analyzes the globalization of world economic ties on the basis of calculation of the globalization index (KOF Index of Globalization), which is calculated by the Swiss Economic Institute.